(3eNJUQ ZfjI GdeJedi TQM efjI GdeUdis - (3EHQGgje GdMdHj , HQgGf GdOjf EHQGgje Hf eMeO Hf EHQGgje GdMdHj,J (B956 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYHGOI eaJGM GdSYGOI hHYO ajbhd EHQGgje Hf eMeO Hf EHQGgje GdMdHi bO cfJ TQMJ cJGH efjI GdeUdi dcf QCjJ ajg HYV (B((3GdEWGdI (B)(3G dJi QHeG ChLHJ aCMHHJ Cf GNJUQ ef aQGFO OdGFdg s
(3BNQgG (B:s
(3hfSCd Gddg JYGdi MSf GdYGbHI dfG hdh GdOjfG hdENhGffG Efg NjQ eSFhd hCcQe eCehd hGdMeO ddg ChdkG hBNQkG hXGgQkG hHGWfkG hSQkG hYdGfjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdg agQS ddcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B66 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B80s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1886s
Keywords: (3Gdabg GdESdGejs